Spatio-temporal modelling of wind speed variations and extremes in the Caribbean and the Gulf of Mexico - Rychlik, Igor; Mao, Wengang (Theoretical and Applied Climatology, 2019)
The wind speed variability in the North Atlantic has been successfully modelled using a spatio-temporal transformedGaussian field. However, this type of model does not correctly describe the extreme wind speeds attributed to tropicalstorms and hurricanes. In this study, the transformed Gaussian model is further developed to include the occurrence ofsevere storms. In this new model, random components are added to the transformed Gaussian field to model rare events withextreme wind speeds. The resulting random field is locally stationary and homogeneous. The localized dependence structureis described by time- and space-dependent parameters. The parameters have a natural physical interpretation. To exemplifyits application, the model is fitted to the ECMWF ERA-Interim reanalysis data set. The model is applied to compute longtermwind speed distributions and return values, e.g., 100- or 1000-year extreme wind speeds, and to simulate random windspeed time series at a fixed location or spatio-temporal wind fields around that location.